Necrotizing Enterocolitis in Very Low Birth Weight Neonates: A Natural History Study - Mara, Kristin C.; Clark, Reese H.; Carey, William A. (American Journal of Perinatology, 2022)
Objective We characterize the most recent natural history of necrotizing enterocolitis (NEC), as this is an essential first step in guiding the prevention and treatment of this disease in the present day.Study Design We performed a retrospective cohort study of neonates who were born at 23 to 29 weeks' gestation and birth weight <1,500 g who received care from the Pediatrix Medical Group between 2004 and 2019. We assessed the incidence of medical and surgical NEC and the patterns of initial antibiotic treatment to develop a contemporary cohort for further analysis. Among patients discharged between 2015 and 2019, we characterized the stage-specific risk factors for patients diagnosed with medical or surgical NEC, as well as patterns of disease onset, progression, biomarkers, and outcomes. We used the same approach to characterize patients diagnosed with suspected NEC.Results Among 34,032 patients in the contemporary cohort, 1,150 (3.4%) were diagnosed with medical NEC and 543 (1.6%) were diagnosed with surgical NEC. The temporal pattern of disease onset was different for medical and surgical NEC, with gestational age– and birth weight–specific risk disparities emerging earlier in surgical NEC. Thirty-day mortality was much greater among surgical NEC patients (medical NEC 16.4% vs. surgical NEC 43.0%), as were rates of various in-hospital and long-term outcomes. Suspected NEC was diagnosed in 1,256 (3.7%) patients, among whom risk factors and disease onset, progression, and outcomes closely resembled those of medical NEC.Conclusion Analyzing data from a contemporary cohort enabled us to characterize the current, stage-specific natural history of NEC, including novel insights into suspected NEC. Future studies could leverage this cohort to characterize how specific patient characteristics, care processes, or biomarkers may influence or predict disease outcomes.Key Points
Keywords: necrotizing enterocolitis; neonate; very low birth weight; prematurity; natural history